Indonesian ID Card Recognition using Convolutional Neural Networks - M. Octaviano Pratama; Wira Satyawan; Bagus Fajar; Rusnandi Fikri; Haris Hamzah (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Indonesian ID Card can be used to recognize citizen of Indonesia identity in several requirements like for sales and purchasing recording, admission and other transaction processing systems (TPS). Current TPS system used citizen ID Card by entering the data manually that means time consuming, prone to error and not efficient. In this research, we propose a model of citizen id card detection using state-of-the-art Deep Learning models: Convolutional Neural Networks (CNN). The result, we can obtain possitive accuracy citizen id card recognition using deep learning. We also compare the result of CNN with traditional computer vision techniques.